Rhizoctonia solani Identified as the Disease Causing Agent of Peanut Leaf Rot in China - Yan, H H (Plant disease, 2013)
Peanut (Arachis hypogaea L.) is one of the most economically important oil crops in the world. Since the 1990s, the peanut industry has developed rapidly in China. However, because of the use of high-yield varieties and increased plant density, a peanut leaf rot disease occurred in Laixi Experimental Fields in Shandong Province, China in 2007. Leaves had nearly circular, brown lesions that enlarged quickly developing yellow-brown halos at the edges of the lesions. High relative humidity under field conditions led to complete necrosis of the leaves with cotton wool-like mycelia observed followed by the development of sclerotia on the leaf surface. Symptomatic plants were observed between 2007 and 2010, and symptomatic leaf tissue was collected from the Laixi Experimental Fields. An isolate (designated YF-1) from symptomatic peanut leaves was isolated and purified on potato dextrose agar (PDA) and water agar (WA) medium. On PDA, the colony appeared initially as colorless and grew to the diameter of a 9-cm petri dish within 3 days. As the mycelium aged, the colony color gradually became light brown, and sclerotia developed on the surface of the colony. YF-1 was identified as Rhizoctonia solani Kühn based on the number of nuclei per cell ranging from 4 to 13 (average 6.1), hyphal diameter being 7.5 to 12.9 μm (average 8.3 μm), branching at right angles, a septum was present near each hyphal branch with a slight constriction, and no clamp connection structures or conidia were ever observed (4). To further confirm the identity of isolate YF-1, genomic DNA was extracted using the DNeasy Plant Mini DNA Extraction Kit (Shanghai Leifeng Biotechnol. Co., Ltd.), and the complete internal transcribed spacer (ITS) region of ribosomal DNA was amplified and sequenced with a pair of primers ITS1/ITS4 (2). A GenBank BLAST search produced an exact match for the sequences of R. solani (AY154301), with 100% sequence similarity. To estimate the mode of anastomosis, YF-1 was paired on WA medium with each reference strain belonging to anastomosis groups (AGs) 1 through 8 (provided by Shandong Agriculture University) (1,3). The results indicated that YF-1 belonged to group AG-1, subgroup AG-1-IA of R. solani. Pathogenicity tests were conducted by inoculating 10 peanut leaves using a colonized paper disc method (filter paper 1 cm in diameter suspended in the mycelia suspension). Ten control leaves received paper discs without mycelium. Inoculated and non-inoculated plants were kept in humid chambers for 24 h at 25°C. Three days after inoculation, the leaves developed typical brown lesions that were similar to those of naturally diseased plants. Koch's postulates were fulfilled by reisolation of R. solani from symptomatic leaves. No symptoms were observed on control leaves. To our knowledge, this is the first report of peanut leaf rot caused by R. solani. Occurrence of the disease in China is a new threat to the health of peanut. References: (1) Y. X. Chen et al. Acta Phytopathol. Sin. 3:139, 1985. (2) T. Misawa and S. Kuninaga. J. Gen. Plant Pathol. 76:310, 2010. (3) A. Ogoshi. Ann. Phytopathol. Soc. Jpn. 38:117, 1972. (4) J. R. Jr. Pameter and H. S. Whitmey. UC Press. 135, 1970